StockLab sebagai Sarana Edukasi Investasi untuk Gen-Z - Perangin-Angin, Naca; Lubis, Tya Wildana Hapsari; Pelawi, Pioner; Situmorang, Iskandar Muda (Universitas Methodist Indonesia, 2025)
Investment education plays a crucial role in equipping young generations like Gen-Z with the knowledge and skills necessary to make informed financial decisions. In the face of increasingly complex economic challenges, a solid understanding of investment can help Gen-Z manage their finances effectively. One innovation in introducing investment in a more engaging way is through educational games like Stocklab, which aims to introduce and enhance Gen-Z's understanding of the fundamental concepts of investment through interactive and enjoyable media for students of SMK N 1 Medan. The results of this community service indicate that the use of Stocklab as a learning tool effectively educates the students of SMK N 1 Medan.